CASE REPORT : RUPTURED CHOLEDOCHAL CYST IN INFANT AND CHILDREN ; 3 CASES - RONGVIRIYAPANICH, Chantima; KEOROCHANA, Sriprapai; SATHORNKICH, Chana (The ASEAN Journal of Radiology, 2023)
Choledochal cysts are uncommon and appear as cystic or fusiform dilatation of the biliary tract including both intra- and extra-hepatic sites. They are usually diagnosed in infancy and childhood. Ruptured choledochal cyst is a rare complication of choledochal cyst. The etiology of ruptured choledochal cyst remain obscure but it may be associated with blunt trauma, cholelithiasis, an additional anatomical abnormality such as ductal stenosis distal to the cyst, or pancreaticobiliary malunion, and inspissated bile. However the cause of rupture is unknown in many cases and is considered to be spontaneous. The perforation site may be single or multiple and mostly in the posterior wall of the cyst. In this report, there were 3 female patients admitted in our hospital with ruptured choledochal cyst type 1. The first and second patients were 3 years old and complained of fever, abdominal pain, and nonbilious vomiting. The third patient, 19 days old, was presented by obstructive jaundice and clinical sepsis. The operative findings of exploratory laparotomy in all 3 patients were saccular dilatation of CBD with intraabdominal bilelike fluid, leading us to make the postoperative diagnosis of ruptured choledochal cyst. The possible causes of ruptured choledochal cyst in the three patients of this report could be cholelithiasis, blunt trauma with a long common channel of the pancreaticobiliary system and inspissated bile respectively. All 3 patients had choledochal cyst typel and were treated by cyst excision in the first operation and Roux-en-Y hepaticojejunostomy in the second operation with good result and no complication.